A New Proxy-Protected Signature Scheme Based on DLP - Swati Verma; Birendra Kumar Sharma (International Journal of Informatics and Communication Technology (IJ-ICT), 2012)
During electronic communication, proxy signature helps the signer to sign message on behalf of the original signer. This type of signature scheme is used when the signatory is not available to sign this document. In this paper, we propose a new protected proxy signature scheme. In the proposed scheme, the proxy signer can sign message on behalf of the original signer with the different type of public key. The proposed scheme satis es unforgeability, undeniability, non-transferability and distinguishability properties which are the most important security requirements for a proxy signature.DOI: http://dx.doi.org/10.11591/ij-ict.v1i2.1479